THE ISSUE OF CIVIL SOCIETY IN THE VIEWS OF ALISHER NAVAI (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
The article analyzes the main ideas regulating the relationship between the citizen and the state in the works of Alisher Navoi. Navoi's works put forward ideas about the need to ensure the stability of society through the spiritual and moral principles of civil society, values such as justice, humanity and equality. He also emphasizes the importance of the principles of honesty, responsibility and social cohesion in public administration, encouraging citizens to be active and strive for knowledge and enlightenment.